Determinant Factor Analysis of Family Psychological Resilience: A Study of Muslim University Staff in Indonesia - Yarmis Syukur; Zadrian Ardi; Triave Nuzila Zahri; Ade Herdian Putra (Islamic Guidance and Counseling Journal, 2023)
A family is a social unit that exists in every culture. Ideally, every family has well enough psychological resilience to achieve prosperity. However, to achieve good psychological resilience, sometimes problems can arise in the family, which is also experienced by Muslim university staff in Indonesia. Three important factors are predicted to correlate with family psychological resilience: family support, economic resilience, and commitment. This study aims to reveal the factors that correlate with the family psychological resilience of Muslim university staff in Indonesia. This study uses a quantitative approach with correlational methods. This research involved 324 Muslim university staff in Indonesia as respondents. The research instruments used were the Family Support Scale, the Family Economic Resilience Scale, the Family Commitment Scale, and the Family Psychological Resilience Scale. Furthermore, the research data analysis used partial least squares structural equation modelling (PLS-SEM) analysis. The results of this study indicate that family support, family economic resilience, and family commitment have a positive correlation and a significant connection with family psychological resilience. These three factors need to be considered in improving the family psychological resilience of Muslim university staff in Indonesia.